InDesign for photographers - Cross, Dave (Peachpit Press, 2008)
"Here is a quick introduction to InDesign with some useful techniques for photographers. Rather than covering all tools and functions of InDesign in detail, this course teaches the basics for photographers so they can get started in creating simple documents using their Photoshop files."--Resource description page